2018
DOI: 10.1111/aji.13056
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy gene ATG5 knockdown upregulates apoptotic cell death during Candida albicans infection in human vaginal epithelial cells

Abstract: Problem Candida albicans infection induces damage in host cells that results in the activation of cell death pathways such as apoptosis and necrosis. Autophagy acts as a pro‐survival mechanism during various infections and has cross talks with apoptosis. The objective of our study was to delineate the effect of autophagy knockdown in human vaginal epithelial cells (VECs) during Candida infection‐induced apoptosis. Method of study We overexpressed wild‐type or mutant form of autophagy‐related gene 5 (ATG5) in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Indeed, only two studies described autophagy activation during the infection of vaginal epithelial cells by C. albicans , an event that improved vaginal cell survival upon infection. 22 , 23 Mucosal epithelial cells are at the frontline of host-microbe interactions and represent initial sentinels and responders to pathogens, thereby contributing to the efficiency of the innate immune response. 24 In the gut, a single layer of epithelial cells confers a physical ( e.g .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, only two studies described autophagy activation during the infection of vaginal epithelial cells by C. albicans , an event that improved vaginal cell survival upon infection. 22 , 23 Mucosal epithelial cells are at the frontline of host-microbe interactions and represent initial sentinels and responders to pathogens, thereby contributing to the efficiency of the innate immune response. 24 In the gut, a single layer of epithelial cells confers a physical ( e.g .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also demonstrated that ATG5 promoted cell apoptosis by activating caspase-8 (37), and that ATG5 is involved in the apoptosis of human cardiomyocytes (38) and colorectal cancer cells (39). The knockdown of ATG5 upregulates the apoptotic cell death of human vaginal epithelial cells (40); moreover, ATG5 suppresses cellular proliferation and induces the apoptosis of dF-1 cells (41). In addition, the inhibition of ATG5 can decrease oxidative stress-based cytotoxicity in osteosarcoma cells (42).…”
Section: Discussionmentioning
confidence: 94%
“…Autophagy remained low in normal rats, implying that probiotics do not need to upregulate autophagy in vaginal mucosa when confronted with inflammatory response and pathogen invasion in the physiological state. Vaginal epithelial cells (VECs) with active autophagy survived the damage caused by C. albicans invasion, indicating that autophagy plays a critical role in the survival of human VECs during infection [16]. Infection with S. aureus, E. coli, or S. agalactiae can activate autophagy in VECs, is not limited to degradation, but instead "hijacks" autophagy, and accelerates proliferation to induce autophagy-dependent host cell death.…”
Section: Discussionmentioning
confidence: 99%